Emerging Trends of Technology-Integrated Problem-Based Learning in Physics Problem Solving: A Bibliometric Analysis (2015–2025) - Anggraini, Ike Nurdela; Dwikoranto, Dwikoranto; Lintangesukmanjaya, Rahmatta Thoriq; Sukarni, Sukarni; Marsini, Marsini; Khansa, Indri Hapsari; Putri, Neisya Azaria Adinda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to map and analyze research trends in technology-integrated problem-based learning (PBL) for physics problem-solving from 2015 to 2025. A quantitative bibliometric design was employed using the Scopus database as the primary data source. An initial search identified 49,401 documents, which were filtered using the PRISMA framework based on relevance, publication year, and screening criteria, yielding 154 publications for the final analysis. Data were analyzed using VOSviewer to examine publication trends, document types, subject areas, country contributions, and keyword co-occurrence networks. Additionally, the ten most highly cited articles were narratively reviewed to identify dominant research directions. The findings reveal a significant increase in publications, particularly in the last two years, indicating rapid growth in this field. Network and overlay visualizations show that problem-solving occupies a central position and is strongly connected to machine learning, deep learning, and intelligent learning systems. At the same time, PBL remains an emerging and less dominant theme. These findings indicate that although research on educational technologies in physics learning is rapidly expanding, the integration of Problem-Based Learning remains limited, highlighting an underexplored intersection between technological advancement and pedagogical implementation in physics education. The study concludes that this gap represents a key direction for future research in strengthening technology-integrated Problem-Based Learning to enhance students’ physics problem-solving skills. Keywords: bibliometric analysis, physics, problem solving, problem-based learning, technology